Life Cycle Assessment of Gayo Arabica Coffee Green Bean at Aceh Province - Pramulya, Rahmat; Tajudin Bantacut; Erliza Noor; Mohamad Yani; Muhammad Romli (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Indonesia's coffee production will reach 774.6 thousand tons in 2021, an increase of 2.75% from 2020, which was 753.9 thousand tons, and is the highest in the last decade and is expected to increase threefold in 2050. Hence, the evaluating environmental performance of the coffee agroindustry is essential if it is to become a more sustainable agroindustry. This paper aims to assess environmental performance (energy footprint, water footprint, and carbon footprint) in Gayo Arabica coffee green bean production with different agro-industry models. The method to evaluate environmental performance that can be used to identify indications of sustainability is Life Cycle Assessment (LCA) Method. The study was conducted on coffee production and exporter cooperatives in Central Aceh. Primary data were obtained through interviews with farmers, collectors, huller owners, and cooperative administrators. Secondary data comes from cooperative reports. The LCA study is described in two product systems, the model of 2015 and the model of 2016. The LCA model of 2015 is based on the green bean production system carried out in 2015 which includes water treatment, pulping, collecting, drying, hulling, finishing, and transportation. The LCA model of 2016 is based on the green bean production system carried out in 2016 until now which includes sub-processes for water treatment, pulping, collecting 1, hulling, collecting 2, finishing, and transportation. The results show that the energy footprint of the 2016 model (2.5128 MJ per f.u) is greater than that of the 2015 model (1.2336 MJ per f.u), the water footprint of the 2015 model is the same as the water footprint of the 2016 model product system, namely 0. 0086 m3 per f.u., and the carbon footprint of the 2016 model (1.93 kg CO2-eq per f.u) is greater than that of the 2015 model (1.48 kg CO2-eq per f.u). The cooperative initiative (in the model of 2016) is for the purpose of process improvement but cannot reduce carbon emissions. To reduce emissions from the use of fossil fuels, it is necessary to optimize land transportation routes and energy efficiency.